Life cycle optimization for sustainable algal biofuel production using integrated nutrient recycling technology - Bello, Muhammadu; Ranganathan, Panneerselvam; Brennan, Feargal P. (American Chemical Society, 2017)
In this study, a multi-objective optimization of sustainable integration of algal biofuel production using nutrient recycling technology, such as anaerobic digestion and hydrothermal liquefaction, is considered. Gross annual profitability and global warming potential (GWP) are the criteria chosen for the design of the algal biofuel production system. Three scenarios, such as full-scale (baseline), pilot-scale (conservative), and lab-scale (nominal), are chosen based on the expected maturity levels and nutrient demand. The results of the optimization produce Pareto sets of optimal solutions for acknowledging the trade-off between the economic and the environmental criteria of the integrated system. It is found that the anaerobic digestion (AD) technology shows better performance in terms of an environmental perspective, displacing the excessive fertilizer requirements due to its maturity in comparison with the hydrothermal liquefaction (HTL) process. However, HTL is a new, evolving, promising nutrient recycling technology which demonstrates economic preferences compared to the AD process due to its low cost of production.
Keywords: Anaerobic digestion; Biofuels; Hydrothermal liquefaction; Life cycle analysis; Multiobjective optimization